Legal Review of the Publication of Song Scores on Youtube Without the Copyright Owner's Permission - Fitriadi, Muhammad; jannah, Miftahul; Marlin, Marlin; Zull Haq, Rusdien Aditya (JUSTITIA JURNAL HUKUM, 2023)
The discussion in this research is fundamentally related to the legal review of the publication of sheet music on YouTube without the permission of the copyright owner. Often uploading song scores on Youtube with the intention of wanting to publish and gain personal gain is a new habit that has been practiced by the public lately because of technological developments and easy access to do so, it also causes a weakness in the legal protection given to creators who own works. and is entitled to the copyright. To examine the themes raised in this study, several main issues were formulated, including 1) What are the indicators of song copyright protection under the Copyright Law?, 2) What are the legal implications for the actions of someone who publishes sheet music without the author's permission in Youtube? The results of this study are that 1) Indicators in song copyright protection based on the Copyright Law, namely moral rights and economic rights. Moral rights are based on the existence of a creation that must be protected because it is a real form of the results of a person's thoughts, imagination, expertise and abilities, while economic rights are based on the existence of exclusive rights that are automatically owned by a creator to benefit from his creation as long as all of these economic rights are not transferred to others. 2) The legal implications arising from the actions of someone who publishes sheet music without the permission of the creator or the legal copyright holder on Youtube, can be sued for civil damages through a commercial court and can also be prosecuted criminally in the form of a criminal act of copyright infringement which is a type of criminal complaint.